Environmental Impact Assessment of Random Landfills in Syrian Coastal Aria: Case study: Al-Hamedia Landfill/ Tartous - ديوب ناجي (Latakia University Journal -Engineering Sciences Series, 2024)
Al-Hamedia Disposal Site is located on the Sea Shore, at the west of Al-Hamedia Road. It is surrounded by water channel from North and South; While Agriculture arias are located from the West. It is about 30 kilometers of Tartous. The Rehabilitation process consist of many stages, which depend on Landfill Age, Waste Type, Aria Topography, Environmental Conditions. It must be taken to account, during the Rehabilitation process, the beautiful, sensitive site of Landfill.Consdering, what has been mentioned above, decreasing the aria of Landfill, is the major aim. And that will be achieved through designing sanitary sale, with all arrangements, such as, leachate collection and treatment, gas system, final cover. Environmental Impact goes through three stages: construction, operation, and management/ monitoring. At the end, the aria must be rehabilitated to reuse as a sandy shore for Tourism purposes.